ANALISA KINERJA SISTEM BILGE PADA JACK-UP DRILLING RIG HASIL DESIGN ULANG - Komarudin, Komarudin; Rahmadan, Syahawirya Ega (Bina Teknika, 2016)
On a project of building jack-up drilling rig CL15 done by PT.X and PT.Y, it uses standard bilge design of PT.X from existing jack-up drilling rig LL90 that has been ever done before. While the design of tanks and compartments CL15 is designed by PT.Y which has differences from the standard of PT.X there is also different rule to be applied . the LL90 uses France class (BV) while CL15 uses American class (ABS). By refering the rule of ABS and hydraulic system theory, the analysis is done covering design and operating capability of bilge system which is done maually so the changes that needs to be applied will be covered to prove that the design of LL90 can be used for CL15 under rule of ABS covering line design, pump capacity, velve selection. Direct suction, head loss, pump pressure which is more efficient